ANALISIS BIAYA POKOK PRODUKSI DAN PENDAPATAN USAHA SUSU KAMBING PERANAKAN ETAWA - Hikemly Ardikha M. Tarigan; Wan Abbas Zakaria; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The study aims to analyze the level of income and standard production cost of etawa goat milk business in the Maju Jaya farmer Group in Batanghari Sub-District, East Lampung Regency. The research method used is a case study in the Maju Jaya farmer Group. Determination of the location of the study was carried out purposively. The total respondents in this study are ten members of Maju Jaya farmer group. Data are analyzed using financial analysis. The results showed that the standard production cost per liter of etawa goat milk is IDR. 14,860. The business of etawa goat milk in the Maju Jaya farmer group is a profitable business. The level of profit, per one goat, generated by farmers is IDR. 1,168,038.50 over cash costs and IDR. 638,281.40 over total costs.Key words: etawa goat, income, standard production cost